Myoinositol causes myometrial contractions in isolated non-pregnant rat myometrium - Kavak, Ebru Çelik; Kaçar, Emine; Kavak, Salih Burçin; Bulmuş, Özgür; Serhatlıoğlu, İhsan; Tektemur, Ahmet (Yuzuncu Yil Universitesi Tip Fakultesi, 2018)
We aimed to investigate myoinositol effect on contractility of rat uterus in vitro and its mechanism of action. In a standard organ bath spontaneous contractions were recorded. After the cessation of spontaneous contractions, 5?M, 50 ?M and 500 ?M of myoinositol and 20?M folic acid were applied to each 7 strips and contractions were again enrolled. Same procedures were also repeated in calcium free solution. Real Time Polymerase Chain Reaction (RT -PCR) analysis of ion channels were done only for 50 ?M myoinositol which corresponds to the treatment dose. It is demonstrated that in all doses increase in frequency and amplitude of contractions were statistically significant. Any contraction was not observed in calcium free solution which demonstrated us that myoinositol uses extracellular calcium for contraction. It is also demonstrated that folic acid does not cause contraction in non pregnant rat uterine smooth muscle cells. Expression of Transient receptor potential cation channel, subfamily M, member 2 (TRPM2) and Transi ent receptor potential cation channel, subfamily V, member 1 (TRPV1) channels significantly decreased after application of myoinositol (p=0.0 1, for both) whereas expression of Transient receptor potential cation channel, subfamily M, member 7 (TRPM7) and C alcium channel, voltage-dependent, N type, alpha 1B subunit (CACNA1B) channels did not change significantly when compared to control (for both). We demonstrated for the first time that myoinositol causes contraction in myometrium of nonpregnant rat uterus and it uses the extracellular calcium for contraction. © 2018, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Contraction; Myoinositol; Rat uterus